Vacuum-assisted biopsy in the era of low-risk ductal carcinoma in situ active monitoring: real world data and implications - Couto, Henrique Lima; Valadares, Carolina Nazareth; Soares, Aleida Nazareth; Ricardo, Bernardo Ferreira de Paula; Toppa, Paola Hartung; Coelho, Bertha Andrade; Pessoa, Eduardo Carvalho; Resende, Vivian; Ferreira, Tereza Cristina de Oliveira; Mattar, Andre; Amorim, Andressa; Clarke, Paula; et al. (Frontiers in Oncology, 2025)
BackgroundThe short-term oncological safe of active monitoring for ductal carcinoma in situ (DCIS) with low risk (LR-DCIS) of progression to invasive cancers (IC) has been demonstrated. This study evaluates vacuum assisted biopsy (VAB) as diagnostic test for LR-DCIS active monitoring (AM) in real-world clinical practice.MethodsDatabase analysis of 116 cancers [both invasive breast cancers (IC) and ductal carcinoma in situ (DCIS)] diagnosed by VAB submitted to standard surgical treatment with complete histological data from VAB and surgery from 04/13/2017 to 11/28/2020. The VAB results matched the surgical pathology, considered the gold standard, and AM criteria. The pathological diagnoses were grouped into malignancies requiring guideline surgical treatment [DCIS with high risk (HR-DCIS) of progression to IC or IC] versus those eligible to alternative AM (LR-DCIS). HR-DCIS/IC were considered positive while LR-DCIS negative results. VAB sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were obtained.ResultsMean age 55.6 [± 12.27]; mean IC size 7.14 [± 5.17]mm and 12.6 [± 11.63]mm for DCIS. Out of 116 malignancies diagnosed by VAB, 15 (12.9%) resulted LR-DCIS in the biopsy, 10 (8.6%) confirmed LR-DCIS in surgery, and 5 (4.3%) upgraded to HR-DCIS/IC in surgery. VAB showed 95.28% (89.3–98.5; 95% CI) sensitivity, 100% (69.2–100; 95% CI) specificity, PPV was 100% (96.4–100; 95% CI), and NPV 66.67% (38.4–88.2; 95% CI). VAB LR-DCIS AM was 6.9% (8/116) and underdiagnoses 2.6% (2 pT1a-bN0 hormone receptor positive and 1 HR-DCIS).ConclusionVAB LR-DCIS AM would lead to a moderate (6.9%) overall reduction of short-term breast cancer surgical overtreatment counterbalanced by a low rate (2.6%) of underdiagnosed HR-DCIS/IC potentially treatable by adjuvant hormone therapy.Clinical Trial Registrationhttps://plataformabrasil.saude.gov.br/visao/pesquisador/gerirPesquisa/gerirPesquisaAgrupador.jsf, identifier 25761019.8.0000.5138.